1998
DOI: 10.1677/joe.0.1570415
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of thyroid-stimulating hormone (TSH) on intracellular free calcium and cAMP in cells transfected with the human TSH receptor

Abstract: The thyroid-stimulating hormone (TSH) binds to a receptor which activates adenylate cyclase and elevates cAMP concentration. In addition, effects of TSH on intracellular calcium and inositol phosphate accumulation have been reported. However, the mechanism of TSH-stimulated accumulation of inositol phosphates and elevation of calcium levels is unresolved. Previous work from this laboratory has shown TSH to cause acute transient increases in intracellular calcium in pig, human and FRTL-5 rat thyroid cells as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Despite the fact that TSH induces the growth of normal thyroid, cancer cell lines of the thyroid frequently escape regulation by TSH. The signaling cascades coupled to the TSHR (Broecker et al 1997, Metcalfe et al 1998 were reported to be defective in WRO (Namba et al 1993), HTh 74 (an anaplastic thyroid cancer cell line) and HTC-TSHr (Broecker et al 1997) cell lines. In the present study, as TSH treatment did not induce either a protein kinase A (cAMP) or a protein kinase C (calcium influx) response, we assumed that the growth-promoting effect was TSHindependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that TSH induces the growth of normal thyroid, cancer cell lines of the thyroid frequently escape regulation by TSH. The signaling cascades coupled to the TSHR (Broecker et al 1997, Metcalfe et al 1998 were reported to be defective in WRO (Namba et al 1993), HTh 74 (an anaplastic thyroid cancer cell line) and HTC-TSHr (Broecker et al 1997) cell lines. In the present study, as TSH treatment did not induce either a protein kinase A (cAMP) or a protein kinase C (calcium influx) response, we assumed that the growth-promoting effect was TSHindependent.…”
Section: Discussionmentioning
confidence: 99%
“…Cell lysates were centrifuged and the supernatants dried in a speed vacuum and re-dissolved in 50 µl Tris-EDTA. With the generation of cellular cAMP, the [ To determine the intracellular calcium concentration, we followed the method described by Metcalfe et al (1998), with minor modifications. Briefly, after reaching 80% confluence on collagen-coated 22 9 mm coverslips, cells were shifted to serum free medium for overnight culture before the assay.…”
Section: Assays For Intracellular Cyclic Amp and Calcium Concentrationsmentioning
confidence: 99%
“…Cells were then washed with balanced salt solution (1.5 mM calcium chloride, 0.5 mM magnesium chloride, 135 mM sodium chloride, 4.5 mM potassium chloride, 5.6 mM glucose, 10 mM Hepes, pH 7.4), and coverslips of cells were examined in a fluorimeter (Kontron SKM 25) to determine changes in intracellular calcium in response to the adenosine agonist PIA (10 mM), and a-MSH (10 À12 M to 10 À6 M) alone or in combination. Details are as previously described in Metcalfe et al (1998).…”
Section: Measurement Of Intracellular Free Calciummentioning
confidence: 99%
“…Cells were washed with PBS, 100 ml ethanol was added and the cells were stored at À201C. Assay details are as previously described (Metcalfe et al, 1998). Extracellular cAMP in the media was determined using a commercially available kit (Biomedical Technologies Inc., USA), in which cAMP measurement is based on competitive binding between cAMP and an alkaline phosphate derivative of cAMP for a limited amount of specific antibody.…”
Section: Measurement Of Campmentioning
confidence: 99%
“…PKC stimulation is important in thyroid cancer because it is the major effector of tumor promoters such as phorbol esters, and its activation leads to proliferation and de-differentiation in FRTL-5 and PC CL3 thyrocytes (60,61). TSHR mediated activation of the PLC-Ca +2 cascade has been controversial because it requires very high TSH concentrations in human primary thyrocytes and in FRTL-5 cells (62-64), however, TSHR clearly increases Ca +2 mobilizations at least in certain contexts such as repeated stimulation or simultaneous activation of other GPCRs (65). Increases in PLC-PKC activities have been reported in thyroid carcinomas (66) but it could be due to activation of other receptors because TSHR is poorly expressed in neoplastic tissue (67); moreover, there is a negative feed back from PKC to PLCβ in thyroid carcinomas (68), and constitutively active mutants of G αq have never been found in thyroid neoplasms (69), although the mutation induces thyroid hyperplasia in mice.…”
Section: Stepmentioning
confidence: 99%